Educational activities on the practice of breastfeeding in a hospital in the interior of Amazonas: an experience report (Research, Society and Development, 2021)
The objective of the work is to describe the experience lived by nursing students during the practice of educational activities on breastfeeding in a hospital in the interior of Amazonas. This is a descriptive study, of the experience report type, about the experience of students from the 9th nursing period, which took place from October 7 to 18, 2019. The public benefited was composed of puerperal women of the Joint Accommodation (CA) of normal delivery and cesarean section. For the execution of the activities, posters on the walls of the ACs were used, with the theme of Breastfeeding being addressed. For academics, this moment resulted in an addition of new experiences, andacquisition of new skills for health education. While the puerperal women reported that health actions aimed at breastfeeding are essential to acquire knowledge about breastfeeding, breast milk and guidelines on the use of objects that interfere with the child's adequate breastfeeding. Such practice provided a unique gain of professional and personal improvement, rich in information and sharing of experiences, which provided knowledge to mother-children and family members, generating a bond of trust with this public.